Risk Factors for Acute Respiratory Infections in Hospitalized Under Five Children in Central Nepal - Yadav, S; Khinchi, Y; Pan, A; Gupta, SK; Shah, GS; Baral, DD; Poudel, P (Journal of Nepal Paediatric Society, 2013)
Introduction: Acute respiratory infection is a leading cause of morbidity and mortality in under 5 children in developing countries. There are various modifiable risk factors associated with Acute Respiratory Tract Infection (ARI). Hence, identification of associated risk factors for ARI may be helpful to reduce the burden of disease. The aims of this study were to study the risk factors for ARI in under five hospitalized children and to correlate risk factors with ARI related morbidity. It was a hospital- based prospective study. Materials and Methods: Children of less than 5 years admitted in ward with diagnosis of ARI were enrolled in the study as cases. Control included children under 5 years of age attending to Well Baby Clinic, Immunization Clinic and siblings or relatives under 5 years who came with patients in the Paediatric outpatient department of the same institution during the same period. Various risk factors, demographic and clinical data of each child were recorded in a pre-designed proforma of both groups. Results: A total of 200 cases and 200 controls were enrolled. The various risk factors associated with ARI on stepwise logistic regression were male gender, rural residency, overcrowding, history of ARI in any family member within two weeks and undernutrition. The statistically insignificant risk factors were infancy, economic status, illiterate parents, cooking fuel other than LPG, low birth weight, prematurity, lack of exclusive breast feeding, vitamin A deficiency and incomplete immunization. Conclusion: The various risk factors for ARI identified in this study were male gender, rural residency, overcrowding, history of ARI in any family member within two weeks and undernutrition. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7358 J Nepal Paediatr Soc. 2013;33(1):39-44